PERAN LEMBAGA PEMBERDAYAAN MASYARAKAT KELURAHAN DALAM MEMBERDAYAKAN MASYARAKAT DI KELURAHAN SUNGAI PAGAR KECAMATAN KAMPAR KIRI KABUPATEN KAMPAR TAHUN 2016 - Winata, Septiani Putri; ", Muchid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Institute Tertasatanatan is a collective organizational implementer representing organizations in and out, in carrying out the task of community empowerment in the village / kelurahan responsible to Village Deliberation / Village. The Village Innovation Institution is also the lowest organization in the organizational structure as the implementer of the community empowerment policy at the village / kelurahan level so that the board is required to have the knowledge and skills and positive attitude especially in carrying out its duties and functions in community empowerment. However, when viewed from the activities of each institution in the village of the river has not been running in accordance with the objectives of its formation, has not run things that are encouraging. The purpose of this research is to know the role of Community Empowerment Institution in Community Empowerment in Sungai Pagar Village Kampar Kiri Subdistrict of Kampar Regency and to know the inhibiting factor of Community Empowerment Institution in Community Empowerment in Sungai Pagar Village Kampar Kiri Sub-district Kampar Regency. When viewed from its type, this research belongs to qualitative research. The results of the research show that the role of Community Empowerment Institution in Community Empowerment in Sungai Pagar Village Kampar Kiri Subdistrict Kampar Regency as Facilitator, Mediator, Motivator and Dinamisator get different result which the role of LPM Sungai Pagar Urban Village has not done its job according to LPM reference. Inhibiting factors The role of Community Empowerment Institutions Village in Community Empowerment in Sungai Pagar Village Kampar Kiri Subdistrict Kampar District is the lack of human resources and the ability of human resources and the absence of sources of funds that can stimulate motivation and provide opportunities LPMK board to work.Keywords : Role , Community empowerment, LPMK